Analysis of logical-dynamic argument conversion processes in arithmetic devices of digital control systems - Al-Suod, Mahmoud M. S.; Ushkarenko, Oleksandr; Petrenko, Lev (Eastern-European Journal of Enterprise Technologies, 2017)
The procedure for analysis of logical-dynamic processes of argument conversion in arithmetic devices of digital control systems was developed. Disadvantages and limitations of the formal methods used to describe processes in control systems were described and a graph-analytical method for describing the processes of argument conversion was proposed. Analysis of the logical-dynamic processes of conversion of data arguments in adders and multipliers used in digital control systems was performed. Sign-positional notation makes it possible to significantly increase speed of adders and multipliers in digital control systems. In this case, a necessity of formation of scientifically substantiated analytical rules for conversion of logical arguments and functional structures through which they are implemented appears. The analytical description of the processes of conversion of information arguments in digital control systems allows one to form their mathematical models with increased technological and informational qualities as well as solve optimization problems. The summation process in arithmetic devices is realized in accordance with the logic of argument conversion of the ternary notation. The axioms of the ternary notation can serve as a theoretical basis of the process of summation of arguments implemented in the binary notation format. The proposed approach enables evaluation of speed of the performed arithmetic operations with the use of various digital codes and opens up the possibility of improving the methods and algorithms of data processing in digital control systems